The Important Role Played by High-Temperature Tensile Testing in the Representation of Minimum Creep Rates Using S-Shaped Curve Models - Mark Evans (Metallurgical and Materials Transactions A, 2023)
It is important to characterize the creep life of materials used in power plants and aeroengines. This paper illustrates the important role played by a material’s tensile strength in enabling accurate creep property representations to be made. It also shows that published high-temperature tensile strength values are not always suitable for use in certain creep models due to its strain rate dependency. To deal with the absence of such suitable date on tensile strength, this paper estimates such values directly from minimum creep rate data. When this technique is applied to models that represent the relationship between minimum creep rates and normalized (with respect to tensile strength) stress using S-shaped curves, an improvement in the fit to data on 2.25Cr–1Mo steel was observed. The findings suggest an important need for future research into the most appropriate strain rates to be used in high-temperature tensile testing when the purpose is to use the resulting tensile strength values for use in creep modeling.